A phase-1 study of dasatinib plus all-trans retinoic acid in acute myeloid leukemia - Redner, Robert L.; Beumer, Jan H.; Kropf, Patricia; Agha, Mounzer; Boyiadzis, Michael; Dorritie, Kathleen; Farah, Rafic; Hou, Jing-Zhao; Im, Annie; Lim, Seah H.; Raptis, Anastasios; Sehgal, Alison; et al. (Leukemia & lymphoma, 2018)
Src family kinases (SFKs) are hyperactivated in acute myeloid leukemia (AML). SFKs impede the retinoic acid receptor, and SFK inhibitors enhance all-trans retinoic acid (ATRA)-mediated cellular differentiation in AML cell lines and primary blasts. To translate these findings into the clinic, we undertook a phase-I dose-escalation study of the combination of the SFK inhibitor dasatinib and ATRA in patients with high-risk myeloid neoplasms. Nine subjects were enrolled: six received 70 mg dasatinib plus 45 mg/m 2 ATRA daily, and three received 100 mg dasatinib plus 45 mg/m 2 ATRA daily for 28 days. Headache and QTc prolongations were the only two grade 3 adverse events observed. No significant clinical responses were observed. We conclude that the combination of 70 mg dasatinib and 45 mg/m 2 ATRA daily is safe with acceptable toxicity. Our results provide the safety profile for further investigations into the clinical efficacy of this combination therapy in myeloid malignancies.